2019
DOI: 10.1016/j.bone.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow adiposity and multiple myeloma

Abstract: Multiple Myeloma (MM) is an incurable haematological malignancy and is the second most common blood cancer in adults; it is caused by the clonal expansion of abnormal plasma cells within the bone marrow and characterized by osteolytic bone lesions, bone pain, renal disease, and immunodeficiency. MM cells infiltrate the bone marrow where they hijack the microenvironment to sustain growth and survival. The contribution to this process by resident bone cells is well defined. However, the role of bone marrow adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
0
15
0
2
Order By: Relevance
“…BM MSCs can differentiate into adipocytes, which increase with age and are considered negative regulators of haematopoiesis (Naveiras et al, 2009). The effects of MM on BM adipocytes remain to be elucidated (Morris & Edwards, 2018). Although adipocytes are evident in interstitial BM and support MM growth in vitro (Trotter et al, 2016;Fairfield et al, 2018), adiponectin, an adipogenic factor, has been shown to induce anti-MM activity and is suppressed in MM (Fowler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…BM MSCs can differentiate into adipocytes, which increase with age and are considered negative regulators of haematopoiesis (Naveiras et al, 2009). The effects of MM on BM adipocytes remain to be elucidated (Morris & Edwards, 2018). Although adipocytes are evident in interstitial BM and support MM growth in vitro (Trotter et al, 2016;Fairfield et al, 2018), adiponectin, an adipogenic factor, has been shown to induce anti-MM activity and is suppressed in MM (Fowler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…BMAT is crucial in the development of blood disease, in which BMAs directly interact with blood tumour cells in the bone marrow. In addition, BMAT has been identified as a key driver in the progression of multiple myeloma [1,18,19].…”
Section: Bone Marrow Adipose Tissue (Bmat) the Third Fat Depotmentioning
confidence: 99%
“…We now showed that post-treatment BM-MSC did indeed differentiate more easily into adipocytes than into osteoblasts. We notably observed that expression of leptin was down-regulated in post-treatment BM-MSC, which was also in favor of the defect in osteogenesis [34]. The ability to better differentiate into adipocytes appeared as soon as MM was diagnosed.…”
Section: Discussionmentioning
confidence: 83%